Pattern Based Usability Testing - Fernando José Dias (2017)
Nowadays it is common the interaction with software systems through graphical user interfaces (GUIs). It is also possible to test applications through the graphical interface, manually or automatically, simulating the actions of the user and evaluating the outcomes obtained through the GUI. Pattern Based GUI Testing (PBGT) is a software testing approach through the graphical user interface based on models, which automates and systematizes the process of the test. PGBT tests the recurring behavior for which it has testing generic techniques (test patterns) able to test different applications after a process of configuration. The subject-matter of this dissertation consists on the implementation of an extension to the PBGT, adding to this tool the possibility to perform usability tests. This report will begin to explore the usability patterns for which it will find generic testing solutions afterwards to test different software applications and thereby, detect usability problems on a website, allowing to evaluate its interaction with the user. The main objective is to extend the PARADIGM language with usability testing patterns and to extend the current environment of PBGT, allowing building models to usability tests. After the implementation, the user will be able to build his own testing pattern with the settings of the web platform he plans to test, managing to obtain a result for the test, which can detect usability problems. One of the innovative aspects of this issue are the new testing patterns and the tool that runs them. This extension will allow the testing of some usability aspects automatically through the graphical user interface. This project is part of Software Engineering's field, more specifically, Software Testing.